Fun learning series: letters to words / Nalini Arumugam ...[et al.] - Arumugam, Nalini; Munchar, Julina; Suppiah, Puspalata C; Subramaniam, Sathiyaperba; Mohd Noor, Maizura (Universiti Teknologi MARA Shah Alam, 2018)
The aim of this study was to develop an interactive learning tool using computer with a view to enhance preschoolers' reading ability in English class. This study adopted an action research methodology addressing the call for more authentic materials for preschoolers to sensitise their curiosity by using authentic objects. This study consisted of two phases; in phase 1, a teacher taught preschoolers basic reading skill by introducing letters and words via printed worksheets while in phase 2, the preschoolers learned the same content via computer. Twelve preschoolers (7 girls and 5 boys) and two teaching staff from Smart Reader Kids participated in this study. The results showed that computer-based learning activities created multi-trial opportunities without any negative interference to the preschoolers. This experiential learning that involved trial and error approach enabled preschoolers to learn independently and at the same time engage in fun-filled activities to self-regulate their learning. Classroom observation further indicated that the preschoolers enjoyed participating in the reading activities designed for them. The use of authentic photographs and visuals in the exercises were appealing and encouraged them to engage in meaningful communication with their peers. In addition, preschoolers displayed a high level of confidence during the lesson as the environment was encouraging without much intervention from the class teacher. This ultimately persuaded the preschoolers to give their own responses while creating opportunity for themselves to explore their own learning.